Challenges in addressing professional competence expectations in human resource management courses. (31st August 2016) - Coetzer, Alan; Ryan, Maria M; Susomrith, Pattanee; Suseno, Yuliani
Abstract : Although research has identified many of the competences that human resource management (HRM) professionals need, limited research examines how competence expectations can be met in HRM courses. This study sought to generate the knowledge required to align HRM courses with competence statements in the recently revised Australian Human Resources Institute Model of Excellence. To accomplish this aim, focus groups and interviews were conducted with HRM professionals from private, public and not‐for‐profit organisations. Findings suggest that the process of aligning course curricula with the MoE is challenging for several reasons, including: competence statements are subject to varied interpretation; subjecting each statement to a learning needs analysis is complex; it is difficult to cluster the wide range of knowledge areas that must be covered into coherent units of learning. This paper explores the appropriateness of using a generic competence model in a curricular‐influencing role and outlines implications of our findings for practice and research. Key points: Using a generic, context‐independent competence model in a curricular‐influencing role may not be appropriate. The process of aligning HRM course curricula with the MoE is challenging. The MoE's potential to impact competencies students bring to workplaces may not be fully realised. Enhancements to the MoE could strengthen its impact on the HRM education agenda.